Vitamin D in Acute Campylobacteriosis–Results From an Intervention Study Applying a Clinical Campylobacter jejuni Induced Enterocolitis Model - Mousavi, Soraya; Lobo de Sá, Fábia Daniela; Schulzke, Jörg-Dieter; Bücker, Roland; Bereswill, Stefan; Heimesaat, Markus M. (Frontiers in Immunology, 2019)
Human Campylobacter infections are progressively rising and of high socioeconomic impact. In the present preclinical intervention study we investigated anti-pathogenic, immuno-modulatory and intestinal epithelial barrier preserving properties of vitamin D applying an acute campylobacteriosis model. Therefore, secondary abiotic IL-10-/- mice were perorally treated with synthetic 25-OH-cholecalciferol starting four days before peroral Campylobacter jejuni infection. Whereas 25-OH-cholecalciferol application did not affect gastrointestinal pathogen loads, 25-OH-cholecalciferol treated mice suffered less frequently from diarrhea in the midst of infection as compared to placebo control mice. Moreover, 25-OH-cholecalciferol application dampened C. jejuni induced apoptotic cell responses in colonic epithelia and promoted cell-regenerative measures. At day 6 post-infection, 25-OH-cholecalciferol treated mice displayed lower numbers of colonic innate and adaptive immune cell populations as compared to placebo controls that were accompanied by lower intestinal concentrations of pro-inflammatory mediators including IL-6, MCP1 and IFN-γ. Remarkably, as compared to placebo application synthetic 25-OH-cholecalciferol treatment of C. jejuni infected mice resulted in lower cumulative translocation rates of viable pathogens from the inflamed intestines to extra-intestinal including systemic compartments such as the kidneys and spleen, respectively, which was accompanied by less compromised colonic epithelial barrier function in the 25-OH-cholecalciferol as compared to the placebo cohort. In conclusion, our preclinical intervention study provides evidence that peroral synthetic 25-OH-cholecalciferol application exerts inflammation-dampening effects during acute campylobacteriosis.